Random poly(ε‐caprolactone‐L‐alanine) by direct melt copolymerization. Issue 11 (11th September 2020) - Salhi, Slim; Mahfoudh, Jihen; Abid, Souhir; Atanase, Leonard‐Ionut; Popa, Marcel; Delaite, Christelle
Abstract: A series of random polyesteramides (PEAs) with a range of molar composition from 90/10 to 50/50 were synthesized by direct melt polycondensation of ε‐caprolactone and l ‐alanine. Their structure was fully characterized by Fourier transform IR and NMR spectroscopy. The resulting copolymers are completely amorphous with the exception of PEA‐90/10 which possesses a semicrystalline structure. These PEAs present increasing glass transition temperatures at increasing l ‐alanine contents and exhibit fairly good thermal stability with 10% mass loss temperatures reaching 315 °C. © 2020 Society of Industrial Chemistry Abstract : Various poly(ε‐caprolactone‐ co ‐l ‐alanine) were synthesized by direct melt polycondensation of ε‐caprolactone and l ‐alanine. Their structure was fully characterized by Fourier transform IR and NMR spectroscopy.